Words and Silences. The Role of Narrative in Abusive Dynamics - Angulo Ordorika, Ianire (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2024)
In abusive dynamics, what is said is as important as what is kept silent. Just as silence plays an essential role in abuses of any kind, so does narrative, which has the capacity to interpret reality and to facilitate or hinder the existence of abusive practices within a human group. A truthful discourse, in the most biblical sense of the term, on the part of all those involved would be conducive to the transformation of an abusive culture into one of care. In this paper, we will illuminate this question of narrative in the light of Scripture and how the word is understood in the biblical tradition. In addition, we will offer two biblical icons, the serpent of Gen 3 and Eliphaz, to illustrate the most frequent features of the discourses of both perpetrators and the community within which abuse occurs.